Wearable Sensing Systems with Mechanically Soft Assemblies of Nanoscale Materials. Issue 9 (19th June 2017) - Lee, Youngsik; Kim, Jaemin; Joo, Hyunwoo; Raj, Milan S.; Ghaffari, Roozbeh; Kim, Dae‐Hyeong
Abstract : Emerging classes of wearable sensing systems that measure motion, physiological, electrophysiological, and electrochemical signals emanating from the human body have driven significant advances in clinical and academic research. These wearable systems rely on important breakthroughs in micro/nano‐electronics, information technology, and materials science. Compared to conventional bulk materials, nanomaterials with zero, one, and two dimensional (0D, 1D, and 2D) architectures exhibit unusual physical properties that could dramatically improve the performance of sensors. By integrating high performance sensors with soft and stretchable electronics, research groups are enabling fully‐integrated multifunctional sensing systems in skin‐worn formats, optimized for managing specific disease models. In this progress report, recent advances in soft wearable sensing systems based on assemblies of 0D, 1D, and 2D nanomaterials, unpackaged integrated circuits, and highly elastic (moisture resistant) encapsulating layers are reviewed. These advanced bioelectronic constructs combine multimodal sensor arrays, data storage elements, wireless data transmission modules, and actuators for continuous monitoring. The soft wearable systems that embody these unusual electronic materials and soft packaging strategies are beginning to impact big data analysis, remote health monitoring, and transdermal drug delivery applications, by transitioning from primary research discoveries to commercial adoption. Abstract : Recent advances in soft bioelectronics technologies have led to new opportunities to integrate electronic components, including sensors, actuators, data storage systems, and wireless data transmission modules with the human body. Here, the latest progress in the development of functional nanomaterials, device design strategies, and fully‐integrated systems, with utility as commercialized products in consumer health and biomedical fields of research, are reviewed.